Hawking's hallway - Shusterman, Neal 1962-; Elfman, Eric 1958- (Disney Hyperion, 2016)
"It is up to Nick Slate to find the last of Nikola Tesla's powerful inventions...or face devastating consequences"...
Keywords: Tesla, Nikola -- 1856-1943 -- Juvenile fiction; Tesla, Nikola; JUVENILE FICTION / Action & Adventure / General / bisacsh; JUVENILE FICTION / Science & Technology / bisacsh; JUVENILE FICTION / Mysteries & Detective Stories / bisacsh; Inventions; Science fiction; JUVENILE FICTION / Action & Adventure / General; JUVENILE FICTION / Science & Technology; JUVENILE FICTION / Mysteries & Detective Stories; Colorado Springs (Colo.); Jugendbuch